The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4088/pcc.08m00744gre
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Adjunctive Aripiprazole in Major Depressive Disorder

Abstract: Objective: To evaluate the safety and tolerability of aripiprazole adjunctive to standard antidepressant therapy (ADT) for patients with major depressive disorder (DSM-IV-TR criteria).Method: Data from 2 identical studies of aripiprazole augmentation (8 weeks of prospective ADT treatment followed by 6 weeks of randomized double-blind adjunctive treatment) were pooled. The incidence of treatmentemergent adverse events (TEAEs) and weight, electrocardiogram (ECG), and laboratory measurements were assessed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In this long-term study, the safety and tolerability of aripiprazole augmentation was demonstrated by relatively low discontinuation rates due to adverse events (23%) over a 52–58-week exposure. Furthermore, the adverse event profile was consistent with that reported in the short-term, double-blind, placebo-controlled trials 23. Most adverse events were mild or moderate in severity and the incidence of serious adverse events was low.…”
Section: Discussionsupporting
confidence: 82%
“…In this long-term study, the safety and tolerability of aripiprazole augmentation was demonstrated by relatively low discontinuation rates due to adverse events (23%) over a 52–58-week exposure. Furthermore, the adverse event profile was consistent with that reported in the short-term, double-blind, placebo-controlled trials 23. Most adverse events were mild or moderate in severity and the incidence of serious adverse events was low.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, Basu and Brar18) suggested that starting aripiprazole at lower doses, either 5 or 10 mg/day, minimizes the risk of akathisia and that starting at doses greater than 30 mg/day increases the risk of schizoaffective disorder. In line with the suggestion by Nelson et al 19). that lowering the starting dose of aripiprazole represents one of the most widely used strategies to minimize the incidence or the severity of akathisia, the results from the present study may reflect clinical experience that a low initial dose could reduce the risk of akathisia.…”
Section: Discussionsupporting
confidence: 90%
“…Most patients had 1 historical treatment failure before entering the trial, and the median duration of the current episode was 21.0 months in the placebo group and 18.8 months in the aripiprazole group. There were no differences between the aripiprazole and placebo groups in the distribution and average dose of each standard antidepressant, 13 and there was no pattern suggesting differential subject disposition for any single standard antidepressant compared with the overall population.…”
Section: Subject Disposition and Characteristicsmentioning
confidence: 96%
“…This pooled safety analysis included 737 patients who received at least 1 dose of study medication (adjunctive aripiprazole, n = 371; adjunctive placebo, n = 366) during the 6-week doubleblind treatment phase. Details of patient disposition and demographic characteristics have been reported previously 13 ; there were no clinically relevant differences between the treatment groups across demographic characteristics. The clinical trial population was predominantly female (64%) and white (88%).…”
Section: Subject Disposition and Characteristicsmentioning
confidence: 98%